153k views
24 votes
Use elimination to solve and please show ur work.
4x + 3y = 6
2x - y = -2

User Peter Zhao
by
4.9k points

2 Answers

9 votes

Answer:

(0,2)

Explanation:

Multiply each equation by the value that makes the coefficients of y opposite.

3*2x-y=3*-2

Simplify

6x-3y=-6

Add the two equations

10x = 0

Divide both by 10 and simplify

x=0

Substitute x into the equations.

4*0+3y=6

3y=6

2

y=2

User Peter Harrison
by
4.9k points
7 votes

Answer:

Add the equations in order to solve for the first variable. Plug this value into the other equations in order to solve for the remaining variables.

Point Form:

(0,2)

Equation Form:x=0, y=2

User Novian Kristianto
by
5.7k points